In situ light‐activated materials for skin wound healing and repair: A narrative review - Jordan R. Yaron; Mallikarjun Gosangi; Shubham Pallod; Kaushal Rege (Bioengineering & Translational Medicine, 2024)
Abstract Dermal wounds are a major global health burden made worse by common comorbidities such as diabetes and infection. Appropriate wound closure relies on a highly coordinated series of cellular events, ultimately bridging tissue gaps and regenerating normal physiological structures. Wound dressings are an important component of wound care management, providing a barrier against external insults while preserving the active reparative processes underway within the wound bed. The development of wound dressings with biomaterial constituents has become an attractive design strategy due to the varied functions intrinsic in biological polymers, such as cell instructiveness, growth factor binding, antimicrobial properties, and tissue integration. Using photosensitive agents to generate crosslinked or photopolymerized dressings in situ provides an opportunity to develop dressings rapidly within the wound bed, facilitating robust adhesion to the wound bed for greater barrier protection and adaptation to irregular wound shapes. Despite the popularity of this fabrication approach, relatively few experimental wound dressings have undergone preclinical translation into animal models, limiting the overall integrity of assessing their potential as effective wound dressings. Here, we provide an up‐to‐date narrative review of reported photoinitiator‐ and wavelength‐guided design strategies for in situ light activation of biomaterial dressings that have been evaluated in preclinical wound healing models.